Improving the Learning Environment of University Science Courses: A Key to Better Elementary Teacher Education. - Martin-Dunlop, Catherine; Fraser, Barry (Key Centre for School Science and Mathematics, Curtin University of Technology, 2006)
This study evaluated the impact of an innovative science course for prospective elementary teachers on their perceptions of the learning environment and compared these perceptions with those of their previous laboratory science course. The sample consisted of 525 female students enrolled in 27 classes of A Process Approach to Science (SCED 401) at a large urban university in Southern California. Perceptions of the learning environment were measured using scales from the Science Laboratory Environment Inventory and What Is Happening In this Class? Attitudes towards science were assessed using one scale from the Test of Science-Related Attitudes. Results indicated that large and statistically significant differences between students’ previous laboratory class and SCED 401 existed for all six learning environment scales. The largest difference was found for the level of Open-Endedness (effect size of 6.74 standard deviations). A statistically significant difference was found for attitude as well. This research makes a distinctive contribution to the learning environments field because it is the first study to investigate laboratory classroom environments at the university level with prospective elementary teachers. The study has implications for undergraduate laboratory course instructors, science teacher educators, and for elementary teachers and the science learning of their students.